2005
DOI: 10.1310/u6uk-abxt-npxw-5l68
|View full text |Cite
|
Sign up to set email alerts
|

Management of Communication Disorders Using Family Member Input, Group Treatment, and Telerehabilitation

Abstract: Today, speech-language pathologists (SLPs) practice stroke rehabilitation in environments where they have less time to manage the communication impairments of patients who are more medically fragile than ever before. Many SLPs have creatively adapted their practice to maximize functional outcomes for their patients. This article highlights three techniques designed to enhance functional SLP outcomes: maximizing family member input; providing group treatment; and providing treatment in remote, functional settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 11 publications
2
12
0
1
Order By: Relevance
“…Investigators at the Rehabilitation Engineering Research Center on Telerehabilitation at the NRH have been at the forefront in technology innovations to deliver services to patients with CVA and TBI. 8,10,14,15 Clinicians in Australia conducted a telerehabilitation pilot study with 19 participants with dysarthria. Results suggested that reliable assessment of motor speech disorders over the Internet is possible in adults with acquired neurological impairment with additional refinement of their technology and assessment protocols.…”
Section: Neurogenic Communication Disordersmentioning
confidence: 99%
“…Investigators at the Rehabilitation Engineering Research Center on Telerehabilitation at the NRH have been at the forefront in technology innovations to deliver services to patients with CVA and TBI. 8,10,14,15 Clinicians in Australia conducted a telerehabilitation pilot study with 19 participants with dysarthria. Results suggested that reliable assessment of motor speech disorders over the Internet is possible in adults with acquired neurological impairment with additional refinement of their technology and assessment protocols.…”
Section: Neurogenic Communication Disordersmentioning
confidence: 99%
“…1,6 Telerehabilitation is an example of using ICT in the field of rehabilitation that saves time and costs and aims to provide the vulnerable populations, for example,, the elderly and disabled people with easier and continued access to healthcare services. 6 Telerehabilitation has been widely used in the treatment of various diseases and health conditions, such as heart attacks, brain injuries, spinal cord injuries, multiple sclerosis (MS), dysphagia, auditory and mental disorders, 7 and several criteria have been examined in different studies to demonstrate the effectiveness of this type of services. For example, telerehabilitation was found effective for patients with MS, as it improved quality of life and functional activities and reduced long-term symptoms and psychological consequences.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, several studies have found that synchronous assessment of aphasia via telepractice is comparable to face-to-face assessment and performance (Brennan et al, 2002;Duffy, Werven, & Aronson, 1997;Hill et al, 2006;Hill, Theodoros, Russell, Ward, & Wootton, 2009;Palsbo, 2007;Theodoros, Hill, Russell, Ward, & Wootton, 2008;Wertz et al, 1992). The few studies examining synchronous telepractice as a means of delivering treatment to PWAs have confirmed its feasibility and user satisfaction and improvement, although there has been no direct comparison of telepractice with in-person therapy (Baron, Hatfield, & Georgeadis, 2005;.…”
Section: Synchronous and Asynchronous Service Deliverymentioning
confidence: 99%